Isolation and optimization for affinity and biophysical characteristics of anti-CCL17 antibodies from the VH1-69 germline gene. Issue 6 (16th April 2014) - Kehoe, John W.; Whitaker, Brian; Bethea, Deidra; Lacy, Eilyn R.; Boakye, Ken; Santulli-Marotto, Sandra; Ryan, Mary H.; Feng, Yiqing; Wheeler, John C.
Abstract: CCL17 is a homeostatic chemokine associated with several human inflammatory pathologies. This makes CCL17 a potential point of intervention in inflammatory diseases. Using a Fab-pIX phage display system we were able to select antibodies that specifically bind to CCL17 and neutralize CCL17-mediated signaling. Many of the selected antibodies belong to the VH 1-69 germline gene family. The VH 1-69 germline gene is represented at a high frequency in the human antibody repertoire and is seen in the early immune response to a variety of pathogens. The heavy chain CDR2 of this germline gene is notably hydrophobic and can insert into hydrophobic pockets of antigens, providing much of the binding energy for these antibodies. Affinity maturation of our primary binders by light chain mutagenesis produced antibodies with sub-nanomolar affinities, with affinity improvements up to 100-fold. These were screened for non-specific protein–protein interactions as a filter for solubility. All of our high affinity antibodies were found to have high levels of non-specific protein–protein interactions. We speculated that this was due to the hydrophobicity within the germline heavy chain CDR1 and CDR2. To ameliorate this problem, we generated a phage display library for one of the clones, where the surface-exposed residues within H-CDR1 and H-CDR2 were randomized. High stringency panning of this library against human CCL17 resulted in further affinity improvement, along with reduction in protein–protein interaction in some new variants. In addition, we improved the cross-reactivity to cynomolgus CCL17. We demonstrate that affinity maturation through targeted libraries in the VH 1-69 germline gene can improve both affinity and biophysical characteristics of antibodies derived from this gene scaffold.